BIBLIOMETRIC ANALYSIS OF DRUG RESISTANCE BIOMARKERS IN BREAST CANCER (2020-2025) - NURSOLEHA, EVA; UTAMI, WAHYU (International Journal of Applied Pharmaceutics, 2025)
Objective: Biomarkers have become critical tools for predicting treatment response and guiding the development of strategies to overcome resistance. This study aims to examine research trends on drug resistance biomarkers in breast cancer from 2020 to 2025, with a focus on identifying key themes, influential authors, contributing countries, and journals contributing to this topic, thus providing insight into ongoing scientific developments and research directions. The bibliometric analysis was conducted using the Scopus database. The search employed the keywords “drug resistance biomarkers” AND “breast cancer,” filtered for open-access articles published between 2020 and 2025 in English. A total of 252 documents were selected based on inclusion and exclusion criteria. Data analysis and visualization were carried out using the Visualization of Similarities viewer (VOSviewer) version 1.6.20, focusing on publication patterns, keyword co-occurrences, and collaboration networks. Out of 1,400 initial records, 252 publications met the inclusion criteria. The year 2022 recorded the highest number of publications. China and the United States emerged as the leading contributors to research on this field. Major contributing journals included Cancers, Frontiers in Oncology and Breast Cancer Research. Prominent research topics included circular RNAs, microRNAs, and protein. Several biomolecules, such as circUBAP2, miR-300, ASF1B, and exosomal Del-1 protein, were identified as key mediators of resistance to chemotherapeutic agents like cisplatin, adriamycin, and paclitaxel. To conclude, this study highlights the potential of specific biomolecules as predictive biomarkers and therapeutic targets for drug-resistant breast cancer. Future research should integrate multi-omics approaches and international collaboration to enhance the clinical translation of these findings and promote personalized treatment strategies.